Buying off the revolution: Democratization, social movements and redistribution - Maria del Pilar López Uribe (London School of Economics and Political Science (LSE), Department of International Development, 2023)
This paper shows that franchise extension is not enough for commitment to redistribution and that in the absence of de facto empowerment, the threat of revolution is intact. In particular, the paper studies the relationship between a democratic reform that extends the political rights of a threatening group and redistribution during periods of revolutionary threat. Far from causing an increase in broad redistribution (e.g. social spending), I show that democratic reform - the state organization of a social movement that extends political rights - can be used to identify rebel leaders and provide private goods to them, in return for preventing social unrest and demobilizing their supporters. I study the context of the organization by the state of the most important social movement in Colombian history - the National Peasant Movement (ANUC) - over almost three decades (1957-1985), in which the threat of a Communist Revolution was perennial and throughout which the government gave ANUC direct political participation at the local level in the executive branch and economic support. Using three newly digitized data sets of Colombian municipalities, I find that rather than leading to broad redistribution to the benefit of the peasantry, the reform instead led to an increase in targeted redistribution in terms of public jobs and lands. In particular, by matching the names of the peasant leaders to the beneficiaries of the land reform, evidence suggests that peasant leaders disproportionately benefited from land reform, especially in municipalities where the communist threat was higher. Finally, I find suggestive evidence that buying off the rebel leaders was an effective counter-revolutionary strategy as it led to fewer revolutionary activities after the support of ANUC was terminated (1972-1985).
Keywords: D70; H76; H41; N46; 330; Threat of Revolution; Democratic Reform; Redistribution; Social Movements; Political Empowerment; Conflict